Adhesively Bonded FRP Reinforcement of Steel Structures: Surface Preparation Analysis and Influence of the Primer - Sourisseau, Quentin; Leprêtre, Emilie; Chataigner, Sylvain; Chapeleau, Xavier; Mouton, Luc; Paboeuf, Stéphane (Volume 1: Offshore Technology, 2022)
International audience In tropical areas, with marine environment, high temperature and humidity, corrosion is a constant threat. The maintenance of steel structures (like FPSO’s) is becoming a challenge. The current technique of “crop and renewing” repair involves a certain number of major issues for project owners such as: “hot work”, that is to say welding; temporary weakening of the structure; need to empty, clean and purging the oil tanks of the FPSO’s, resulting in long downtime and an expensive solution. “Cold repair”, such as composite repair, is a promising solution. However, surface preparation and the influence of the primer are crucial issues to be addressed to ensure the strength and reliability of this type solution based on bonded patch. The paper presents an experimental study of the influence of the surface preparation and the primer on the strength of small steel bonded specimens which have been deliberately degraded by corrosion and pollution. Several surface preparation methodologies were investigated and the quality of these preparations was assessed using methods that can be implemented on site. Two main aspects were investigated: the detection of the residual presence of pollutants through the use of a portable infrared spectrometer; and the determination of surface energy after preparation using contact angle and wettability measurement equipment. To study the impact of the primer on the adhesion capacity of the steel surface, critical toughnesses measurements was performed with End notch flexure tests. Three configurations have been tested: bonding with the epoxy resin without initial application of primer and bonding with the Epoxy resin with initial application of two Primer A and B. The results shown clearly that the type of primer and the quality of its application are paramount importance to ensure the strength of steel bonded patches.